2019
DOI: 10.14569/ijacsa.2019.0100538
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Machine Learning Techniques on Software Defect Prediction using NASA Datasets

Abstract: Defect prediction at early stages of software development life cycle is a crucial activity of quality assurance process and has been broadly studied in the last two decades. The early prediction of defective modules in developing software can help the development team to utilize the available resources efficiently and effectively to deliver high quality software product in limited time. Until now, many researchers have developed defect prediction models by using machine learning and statistical techniques. Mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
110
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(114 citation statements)
references
References 28 publications
0
110
0
4
Order By: Relevance
“…We have used D'' (Table 1) version in this research which is taken from [22]. These cleaned datasets are already used and discussed by [5,6], [23,24,25], [35]. Data Preprocessing is the second stage of proposed framework which consists of feature selection and class balancing activities.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have used D'' (Table 1) version in this research which is taken from [22]. These cleaned datasets are already used and discussed by [5,6], [23,24,25], [35]. Data Preprocessing is the second stage of proposed framework which consists of feature selection and class balancing activities.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the proposed framework outperformed other classification techniques in some of the datasets. Researchers in [6] compared the performance of various supervised machine learning techniques on software defect prediction including: "Naïve Bayes (NB), Multi-Layer Perceptron (MLP). Radial Basis Function (RBF), Support Vector Machine (SVM), K Nearest Neighbor (KNN), kStar (K*), One Rule (OneR), PART, Decision Tree (DT), and Random Forest (RF)".…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations